Evaluation of air compressibility effects on the performance of fixed OWC wave energy converters using CFD modelling. (April 2018) - Simonetti, I.; Cappietti, L.; Elsafti, H.; Oumeraci, H.
Abstract: This study presents an evaluation of the error induced by neglecting the effect of air compressibility in modelling Oscillating Water Column (OWC) wave energy converters. A compressible two phases CFD model in the open-source software package OpenFOAM ® is validated and then used to simulate a fixed OWC device, detached from the sea bottom. A comparative analysis of the results obtained by simulating the device at full-scale (1:1) and at four smaller scales (1:50, 1:25, 1:10 and 1:5) is performed in order to assess the scale effects associated with air compressibility. Indeed, for the air pressure levels considered in the simulations (up to 350 Pa at model scale 1:50), the effect of neglecting the air compressibility results in an overestimation up to about 15% for the air pressure in the OWC chamber and the subsequent air volume flux, but less than 10% for the capture width ratio. This overestimation increases with increasing pressure level. Results are analysed in terms of dimensionless parameters and a new parameter, strongly related to the compressible effects, is proposed and used to provide generalized equations delivering correction factors. Highlights: The errors induced by neglecting the effect of air compressibility in modelling OWC devices are quantified. The study is based on multiphase, compressible CFD modelling of the OWC device at scale 1:50, 1:25, 1:10, 1:5 and 1:1. Neglecting air compressibility results in an overestimation up to 15% for the OWC air pressure, but less than 10% for the capture width ratio. A new dimensionless parameter is proposed to provide generalized equations delivering correction factors for OWCs. These equations might be useful to correct results of incompressible numerical models or small-scale laboratory tests of OWCs.